KOMPARASI KONSENTRASI HIDROGEN SENSOR MQ-2 TERHADAP LUAS DAN WARNA NYALA API HASIL ELEKTROLISIS AIR - Bernardus Crisanto Putra Mbulu; Danang Murdiyanto; Mietra Anggara (Scientific Journal of Mechanical Engineering Kinematika, 2023)
Hydrogen is a fuel that is being developed today as a substitute for fossil fuels that are depleting. One way to produce hydrogen fuel is through the electrolysis method using a water-based HHO generator. This study aims to determine how much hydrogen is produced from each electrolyte solution, which is then compared to the area and color of the resulting flame. The comparison of each electrolyte solution comes from the ratio of moles of solute and solvent (H2O), which is 1:12, with the solutes used being NaCl, CH3COOH, and NaHCO3. The concentration of hydrogen gas produced is detected using the MQ-2 sensor. At the same time, the area and color of the flames are obtained through the results of a 20-minute combustion video, which is made into 100 photo frames for each electrolyte solution. The results of this study showed that the average hydrogen production for NaCl solute was 891.0 ppm and the flame area was 12.64 mm2 without blue color, the solute CH3COOH was 917.33 ppm, the flame area was 16.46 mm2 with 40.52% blue color, and NaHCO3 solute was 980.67 ppm with a flame area of 17.47 mm2 with 76.19% blue color